(untitled) (Research, Society and Development, 2022)
Due to the increase in the practice of the crime of improper use of privileged information, known as insider trading, it was decided to carry out a historical survey related to the ways of combating crime in North America, as well as a study of the historical and legislative evolution in the Brazil in order to present how the problem is being conducted in the country. A bibliographic, doctrinal and jurisprudential review and presentation of results in a descriptive way were used as a method for data collection. It was concluded that in Brazil the misuse of privileged information is punished at the administrative level, by means of a warning, fine and suspension of the exercise of an administrative position; in the civil sphere, through indemnity sanctions and, in the criminal sphere, with imprisonment from 1 to 5 years and a fine of up to 3 times the amount obtained as an advantage. Law no. 10,303/2001 simplified the criminal type, aiming to incriminate all offenders. However, because it is a complex crime and difficult to prove, it is observed in practice a reduced number of convictions. Constant technological advances provide new modalities of operations in the securities market, making the activities of supervision, inspection and application of penalties increasingly challenging.